2019
DOI: 10.1186/s13104-019-4186-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis among adult patients with diabetes mellitus admitted to emergency unit of Hawassa university comprehensive specialized hospital

Abstract: ObjectiveThis study was aimed to assess the prevalence and associated factors of diabetic ketoacidosis among adult patients admitted in emergency department of Hawassa university comprehensive specialized hospital. An institution based retrospective cross-sectional study design was conducted among 195 adult patients aged 16 years and above with known or previously unknown diabetes cases presented in the emergency unit.ResultIn our study from the total 195 patients medical record reviewed 78 (40%) developed DKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 12 publications
(23 reference statements)
2
27
3
3
Order By: Relevance
“…A similarly high rate of diabetic ketoacidosis was observed by Besado and colleagues. 13 Also, there is a trend of increasing admission for ketoacidosis in the last two decades. 14 A strong contributor to poor glycaemic control and possible ketoacidosis in the current study could be that nearly one in five of patients were not estimating the glycated haemoglobin regularly, overtreatment of a hypoglycaemic attack may lead to high blood sugar.…”
Section: Discussionmentioning
confidence: 99%
“…A similarly high rate of diabetic ketoacidosis was observed by Besado and colleagues. 13 Also, there is a trend of increasing admission for ketoacidosis in the last two decades. 14 A strong contributor to poor glycaemic control and possible ketoacidosis in the current study could be that nearly one in five of patients were not estimating the glycated haemoglobin regularly, overtreatment of a hypoglycaemic attack may lead to high blood sugar.…”
Section: Discussionmentioning
confidence: 99%
“…DKA is no more considered as a metabolic emergency of only T1D (Bedaso et al 2019;Jabbar et al 2004;Takeuchi et al 2017;Mudly et al 2007). It is estimated that out of all DKA cases, around 34% occur in T2D (Kitabchi et al 2009 (Fig.…”
Section: Epidemiologymentioning
confidence: 99%
“…1,[9][10][11] Ethiopia is the leading country in Sub-Saharan Africa (SSA), with over 2.6 million adult diabetes patients; with an estimated diabetes prevalence of 5.2% in 2017, 1,3 probably catalyzed by economic and societal transitions, and childhood malnutrition, with about 70% of adults with undiagnosed diabetes. 1,10,12 Recent studies in Ethiopia [13][14][15] indicated that more than one-third of patients admitted with hyperglycemic emergencies were undiagnosed diabetes, which suggests people die undiagnosed and the prevalence of diabetes could be beyond this magnitude.…”
Section: Introductionmentioning
confidence: 99%